Transformation Of The Role Of Technology In The Collection And Distribution Of Social Funds - Putri Kartini, Kharisma; Muarrifah, Safrina (Riviera Publishing, 2023)
Digitalization of zakat and waqf is an innovation that has great potential to encourage the empowerment of the people. Through literature analysis and case studies, this research explores the role of zakat and waqf in Islam, the development of their digitalization in Indonesia, and how this innovation helps in the process of empowering the Ummah. This study aims to examine the transformation of the role of technology in the collection and distribution of social funds, especially related to the digitalization of zakat and waqf in Indonesia. The formulation of this research problem is focused on how digital technology has changed the way zakat and waqf are collected and distributed, as well as its impact on the effectiveness and efficiency of this process. The method used is descriptive analysis, where data and information are collected through relevant literature studies, as well as observations of the implementation and current practices of digitalizing zakat and waqf in Indonesia. Although there are challenges, such as the need to increase digital literacy and transparency, digitalization can be an essential force in maximizing the distribution and effectiveness of zakat and waqf. Solutions and steps that can be taken to overcome these challenges are also discussed. Therefore, collaboration between the government, financial institutions and zakat and waqf management organizations is essential in realizing the full potential of this digitalization.